Experience Since MELD Implementation: How Does the New System Deliver? - Markus Quante; Christoph Benckert; Armin Thelen; Sven Jonas (International Journal of Hepatology)
Because of increasing waiting-list mortality, the MELD (Model for End-Stage Liver Disease) allocation system was implemented within most countries of the Eurotransplant area on December 16, 2006. Five years have now passed, and we review in this paper the effects of the MELD-based allocation upon the waiting list for liver transplantation, on peri-operative management and on postoperative outcome. Giving priority to sicker patients on the waiting list has resulted in a significant increase in mean MELD score at the time of organ allocation. Consequently, there has also been a significant reduction in waiting-list mortality. However, in Germany a worsening in postoperative outcome, mainly in the group of high-MELD recipients (30 points), has been reported. This paper presents comprehensive results following liver transplantation within the MELD era. Especially for the group of high-risk recipients, risk factors for impaired survival are presented and discussed.